Toxicological and anti-hyperglycemic studies of five plants used for the treatment of type 2 diabetes in Benin - SETON, Santorin; KOUKOUI, Omédine; AMAGBEGNON, Jean Baptiste; BETIRA, Mansouratou; SONOUNAMETO, Fidèle; ASSOU, Eudoxie; SEZAN, Alphonse (Journal of Drug Delivery and Therapeutics, 2022)
In Benin as in the African sub-region, the burden of Non-Communicable Diseases (NCDs) and the threats they represent constitute a major public health problem which hinders their economic and social development. NCDs kill 36 million people each year and 80% of deaths occur in developing countries, including Benin. The objective of our work is to evaluate the acute, subacute toxicity and the anti-hyperglycemic activity of five plants listed through an ethno pharmacological survey which is used for the treatment of type 2 diabetes in Benin. The acute toxicity test was conducted on male and female wistar rats at a single dose of 2000 mg/kg. The subacute toxicity test was carried out over a period of 28 days, with 6 batches of 3 rats. Batch 1 received daily 1 ml/100 g of distilled water and batches 2, 3, 4 and 5 respectively the leaf extracts of Bambusa vulgaris Schrad. Ex-Wendel; Parkia biglobosa (Jacq.) R. Br. Ex G. Don; Mangifera indica L.; Saccharum officinarum L.; And Annona muricata L. at a daily dose of 200mg/kg per day for 28 days. Administration of the single dose of the extract did not cause any deaths. In rats treated with repeated doses of 200mg/kg for 28 days the variation in weight depends on the extracts. The level of transaminases (AST and ALT) did not vary. Plant extracts did not induce any significant change in creatinine level. All five extracts have anti-hyperglycemic activity. Our results allow us to deduce that these plants can be used to prevent and treat diabetes without the risk of hepatic and renal toxicity.Keywords: Medicinal plants; Type 2 diabetes; Toxicity; efficacy